Proposing a Suitable Integrated Model of Cooperative Learning Styles and Its Impact on Academic Achievement and Mathematics Anxiety Among Ninth-Grade Students: A Mixed-Methods Study - Shahrabi Farahani, Ali; Keramati, Mohammad Reza; Javadipour, Mohammad; Salehi, Keyvan (Iranian Journal of Educational Sociology, 2025)
Purpose: This study aimed to evaluate the effectiveness of an integrated cooperative learning model in reducing mathematics anxiety and enhancing academic achievement among ninth-grade students.Methods and Materials: A mixed-methods exploratory research design was employed. In the qualitative phase, a conceptual framework was developed by synthesizing cooperative learning strategies from existing literature and focus group interviews with educators. The final model incorporated multiple cooperative strategies, including the jigsaw method, problem-based learning, team games tournament, and peer teaching. In the quantitative phase, a quasi-experimental method with pretest-posttest and control group design was used. Sixty ninth-grade students from two mathematics classes in Tehran were randomly assigned to either the control group (traditional instruction) or the experimental group (integrated cooperative model). Mathematics anxiety was measured using a standardized questionnaire, and academic achievement was assessed through math tests. Data were analyzed using ANCOVA to control for pretest differences.Findings: ANCOVA results indicated a significant effect of the integrated cooperative learning model on reducing mathematics anxiety, F(1, 57) = 83.449, p < .001, with a large effect size (η² = 0.594). Additionally, a significant improvement in academic achievement was observed in the experimental group compared to the control group, F(1, 56) = 6.236, p < .001, with a moderate effect size (η² = 0.100).Conclusion: These findings support the use of structured, student-centered, and collaborative instructional methods as viable alternatives to traditional teaching, particularly in mathematics classrooms where anxiety and low achievement are prevalent.